Environmental Impact of Genetically Modified Crops - Ferry, Natalie (CABI, 2014)
World population increased fourfold during the last century, with current estimates placing it at 9.2 billion by 2050. We are now facing a situation where food demand is beginning to outstrip supply, a scenario predicted some two centuries ago by the Reverend Robert Malthus (Jesus College Cambridge; 1766–1834). This situation is compounded by the fact that we may be at the limit of the existing genetic resources available in our major crops (Gressel, 2008). Thus, new genetic resources must be found and only new technologies will enable this.